PERSPECTIVES ON TEACHING AMONG SERBIAN UNIVERSITY TEACHERS WITHIN THE FIELD OF THE SOCIAL SCIENCES AND HUMANITIES. - MILUTINOVIC, Jovana; PEKIC, Jasmina; LUNGULOV, Biljana (Studii de Ştiintă şi Cultură, 2022)
The issue of pedagogical training of university teachers is important in the context of considering possibilities of improving the quality of higher education. This paper, based on the conceptual and empirical framework of five perspectives on teaching, aims to determine the representation of perspectives on the teaching of university teachers in the field of social sciences and humanities in Serbia. The Teaching Perspectives Inventory (TPI) was used as an instrument on a sample of 159 university teachers and associates. The research confirmed the presence of five perspectives on teaching; compared to the results of previous research, only minor differences in their expression were observed. The findings indicate the need to take different cultural contexts of higher education into account when designing the program of pedagogical education of university teachers.